Pinnacle on the Mound: Cy Young Award Winners Talk Baseball - Wedge, Doug, (Rowman & Littlefield Publishers, 2022)
Cy Young Award winners spanning fifty years of baseball history reflect on their iconic seasons, keys to success, and most memorable moments. In Pinnacle on the Mound: Cy Young Award Winners Talk Baseball, ten pitchers who were recognized as the best in the game share fascinating stories from their years in the majors. Featuring pitchers such as Hall of Famer Dennis Eckersley and five-time Gold Glove Award winner Ron Guidry, this bookoffers captivating insight into the players’ different approaches to the game, how they honed their skills, and what was happening behind the scenes in their award-winning seasons. From fastballs to sinkers, curveballs to knuckleballs, this diverse group of pitchers found success in many different ways, whether it was mastering a new pitch or taking on the role of a closer. Including All-Stars Jim Lonborg, Mike McCormick, Randy Jones, Ron Guidry, LaMarr Hoyt, Dennis Eckersley, Jack McDowell, Barry Zito, R.A. Dickey, and Corey Kluber, Pinnacle on the Mound makes fifty years of baseball history come alive.